The Effect of Green Accounting, Good Corporate Governance Mechanism and Corporate Social Responsibility on Company’s Financial Performance of Company Listed on the Indonesia Stock Exchange 2020-2022 - Ariansyah, Rudy; Bintara, Rista (Monas: Jurnal Inovasi Aparatur, 2025)
This study aims to analyze the effect of Green Accounting, Good Corporate Governance Mechanism and Corporate Social Responsibility on Company’s Financial Performance (Empirical Study of Company Listed on the Indonesia Stock Exchange 2020-2022). The population in this study are company listed on the Indonesia stock Exchange that participated to The Public Disclosure Programme for Environmental Compliance (PROPER) by the Ministry of Environment and Forestry in the period 2020-2022 period totalling 86 companies by using purposive sampling technique. 65 companies were selected as sample. This study used panel data regression as the anlysis methode with software Eviews 12. The result showed that green accounting¸ managerial ownership, independent commissioners, audit committee and corporate social responsibility have positive effect on company’s financial performance.